2014
DOI: 10.1111/pce.12353
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characterization and genetic modifiers of aberrant root thigmomorphogenesis in mutants of Arabidopsis thalianaMILDEW LOCUS O genes

Abstract: Root architecture and growth patterns are plant features that are still poorly understood. When grown under in vitro conditions, seedlings with mutations in Arabidopsis thaliana genes MLO4 or MLO11 exhibit aberrant root growth patterns upon contact with hard surfaces, exemplified as tight root spirals. We used a set of physiological assays and genetic tools to characterize this thigmomorphogenic defect in detail. We observed that the mlo4/mlo11-associated root curling phenotype is not recapitulated in a set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 74 publications
1
40
0
1
Order By: Relevance
“…Several previously known genes for controlling the RSA were identified. We found an upregulation of MLO 14 like protein in root, a recent study of MLO mutant revealed its involvement in polar auxin transport which is one of the components jointly responsible for an aberrant root phenotype 65 . A channeling protein, Annexin (ANNAT7) is reported to be involved in lateral root development by modulating the Ca 2+ ion gradient 66, 67 .…”
Section: Discussionsupporting
confidence: 55%
“…Several previously known genes for controlling the RSA were identified. We found an upregulation of MLO 14 like protein in root, a recent study of MLO mutant revealed its involvement in polar auxin transport which is one of the components jointly responsible for an aberrant root phenotype 65 . A channeling protein, Annexin (ANNAT7) is reported to be involved in lateral root development by modulating the Ca 2+ ion gradient 66, 67 .…”
Section: Discussionsupporting
confidence: 55%
“…MLO4 and MLO11 are involved in modulating root thigmomorphogenesis. In mlo4 and mlo11 mutants, roots grow in a tightly curled pattern; this anisotropic chiral root expansion phenotype requires polar auxin transport and calcium signalling (Bidzinski et al, ; Chen et al, ). Mechanical stimulation of Arabidopsis roots results in a specific signature of calcium transients that further triggers apoplastic alkalinization and RBOHC ‐dependent ROS accumulation, transmitting touch stimuli into appropriate growth responses (Monshausen, Bibikova, Weisenseel, & Gilroy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond MLO2, MLO6, and MLO12, few functions of other Arabidopsis MLO genes are known. MLO4 and MLO11 are involved in modulating root thigmomorphogenesis (Bidzinski et al, 2014;Chen et al, 2009) and MLO7 in the regulation of pollen tube growth (Kessler et al, 2010).…”
mentioning
confidence: 99%
“…1c). When grown in vitro, Atmlo4 and Atmlo11 null mutants display unusual root curvature, evident as severe root curling, upon a tactile stimulus (Chen et al, 2009;Bidzinski et al, 2014;Fig. 1b).…”
Section: Do You Want To Know a Secret: Mlo Function Is Not Restrictedmentioning
confidence: 99%